2006
DOI: 10.1021/ie051211l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preparation Temperature on Cyclic CO2 Capture and Multiple Carbonation−Calcination Cycles for a New Ca-Based CO2 Sorbent

Abstract: The cyclic CO2 capture, transient phases change, and microstructure appearance of a new kind of Ca-based regenerable CO2 sorbent, CaO/Ca12Al14O33, obtained by the integration of CaO as solid reactant with a composite metal oxide of Ca12Al14O33 as a binder, were investigated by thermogravimetric analysis, XRD, and SEM at different preparation calcination temperatures. When the calcination temperature in the preparation stage is higher than 1000 °C, the cyclic CO2 capture of this new sorbent declines. The lowere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
244
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(256 citation statements)
references
References 26 publications
8
244
1
3
Order By: Relevance
“…with CaO (Aihara et al, 2001;Salvador et al, 2003;Roesch et al, 2005), some additives were found to be destructive or disadvantageous to the stability of adsorbents (Hasler et al, 2003;Lu et al, 2006) and to increase equipment capacity as well as operation cost. The modification of pore structure could be achieved by incorporation of Al into CaO to form mayonite (Ca 12 Al 14 O 33 ) (Li et al, 2006;Martavaltzi and 1: Propane tank; 2: Coil; 3: Syringe pump; 4: Valves; 5: Reactor; 6: Pressure gauge; 7: Thermocouple; 8: Heating tape; 9: Ice bath; 10: Oven. Fig.…”
Section: Other Adsorbentsmentioning
confidence: 99%
“…with CaO (Aihara et al, 2001;Salvador et al, 2003;Roesch et al, 2005), some additives were found to be destructive or disadvantageous to the stability of adsorbents (Hasler et al, 2003;Lu et al, 2006) and to increase equipment capacity as well as operation cost. The modification of pore structure could be achieved by incorporation of Al into CaO to form mayonite (Ca 12 Al 14 O 33 ) (Li et al, 2006;Martavaltzi and 1: Propane tank; 2: Coil; 3: Syringe pump; 4: Valves; 5: Reactor; 6: Pressure gauge; 7: Thermocouple; 8: Heating tape; 9: Ice bath; 10: Oven. Fig.…”
Section: Other Adsorbentsmentioning
confidence: 99%
“…Reproduced with permission from Elsevier. (Li et al, 2006), CuO/CaO composite (Manovic et al, 2011), CaO calcined from mesoporous CaCO 3 (Iyer et al, 2004), thermal pretreatment of CaO (Can Ozcan et al, 2011), and CaO prepared with various precursors (Lu et al, 2006). This summary of the kinetic analyses demonstrates that the kinetics of the calcination and carbonation reactions vary widely depending on the sorbent source and gas atmosphere composition.…”
Section: Sorbent Degradationmentioning
confidence: 88%
“…Cycling studies of natural limestone show its capacity to reduce by as much as 90 mol% aer only the rst 20 cycles owing to sintering. 5 While one focus of recent research has been to alter the properties of CaO through synthetic methods with different additives such as Al 3 O 3 , Ca 12 Al 14 O 33 , or SiO 2 , [6][7][8] there is still a fundamental lack of understanding regarding how the carbonation reaction proceeds and what parameters control the function of absorbent materials.…”
Section: Introductionmentioning
confidence: 99%